Venture capital as innovative source of financing equity capital after the financial crisis in Spain - Fauna Atta Frimpong; Ellis Kofi Akwaa-Sekyi; Frank Gyimah Sackey; Ramon Saladrigues Solé (Cogent Business & Management, 2022)
The global financial crisis affected the supply of funds to finance equity capital, thus calling for innovative risk capital financing methods. The paper explores the sources of venture capital (VC henceforth) fundraising and determines the relationship between VC fundraising, stock market returns, and market capitalization in Spain. The study uses time-series data of VC fundraising and stock market variables from 1989 to 2020 in a vector error correction model analysis after performing cointegration. The paper reports short-run and long-run causal relations between VC fundraising, stock market returns, and market capitalization when VC fundraising and stock market returns are used as dependent variables. However, such relations do not exist when the model is dependent on market capitalization. Our results show that the VC market raises funds from diversified (geographical and institutional) sources. Our findings support the risk diversification theory of VC financing. The paper provides implications for using alternative innovative ways of financing equity risk capital to spur economic growth.
Keywords: 650; Venture capital; Equity financing; Fundraising activities; Spanish economy; Stock market returns